Head‐to‐head comparison of acute and chronic pulmonary vein stenosis for cryoballoon versus radiofrequency ablation. Issue 4 (27th February 2018) - Watanabe, Ryo; Sairaku, Akinori; Yoshida, Yukihiko; Nanasato, Mamoru; Kamiya, Hiroki; Suzuki, Hirohiko; Ogura, Yasuhiro; Aoyama, Yutaka; Maeda, Mayuho; Ando, Monami; Eguchi, Shunsuke; Inden, Yasuya; et al.
Abstract: Background: Cryoballoon (CB) applications to pulmonary veins (PVs) can cause stenosis just as radiofrequency (RF) energy deliveries. The goal of the present study was to clarify whether or not there was any difference in the extent of acute or chronic PV narrowing after PV isolation between the two different energy sources. Methods: Consecutive patients with paroxysmal atrial fibrillation who were scheduled to undergo a PV isolation were randomized 1:1 to receive CB or RF ablation. The endpoints were any acute PV narrowing assessed with the use of intracardiac ultrasound during the procedure and PV stenosis measured with cardiac computed tomography at the 3‐month follow‐up. Results: An acute reduction in the luminal area of the left superior PV (mean ± standard deviation, –6.8 ± 8.7 vs –19.9 ± 14.7%; P < 0.001) and left inferior PV (–5.1 ± 20.2 vs –15.3 ± 11.6%; P = 0.03) was significantly smaller in the CB arm (N = 25) than the RF arm (N = 25). There was no difference in the extent of PV stenosis 3 months after the ablation between the arms (0–25% stenosis, 90% vs 88%, 25–50% stenosis, 10% vs 12%,  >50% stenosis, both 0%; P = 0.82). A greater acute PV narrowing was likely to lead to chronic stenosis in the RF arm (P = 0.004). Conclusions: CB ablation may reduce the acute narrowing of the left‐sided PVs as compared to RF ablation.